An Association Study of Cervical Cancer Correlated with The Age of Coitarche in Dr. Soetomo Hospital Surabaya - Dewi Sulistyawati; Zakiyatul Faizah; Eighty Mardiyan Kurniawati (Indonesian Journal of Cancer, 2020)
Background: Cervical cancer is one of the deadliest diseases for women’s lives. It is estimated that almost every hour, one died because of cervical cancer and 70% of new cases are found in an advanced stage. Many factors could cause cervical cancer, one of the risk factors is the age of the early coitarche. This study aims to determine the association between the age of coitarche and cervical cancer.Methods: This study was an analysis of observational study with a case-control design. There were two groups in this study; the case group of outpatients who were diagnosed with cervical cancer and the control group of outpatients who had normal cervical cytology by Papanicolaou screening. The 39 respondents of both the control and case groups, calculated using the Lemeshow’s formula for consecutive sampling, were interviewed for their details concerning reproductive and sexual histories, socio-economic status, hygiene, and education. The independent variable in this study was the age of coitarche; the dependent variable was cervical cancer. The data were analyzed descriptively and using the bivariate analysis (Chi-square) with α=0.05.Results: It is identified that 39 respondents for each group (case and control) have almost the same percentage of the age of coitarche in One-Stop Oncology Polyclinic (POSA’s outpatient); early coitarche of 43.6% and late coitarche of 56.4%. The age of early coitarche in Obstetrics and Gynecology’s outpatients, as a control group, is rare (4 of 39 respondents; 10.3%) and most of them did their sexual debut at the age of >18 years (89.7%). The chi-square test showed there was a correlation between the age of coitarche and cervical cancer (P=.002; OR=6.76; 95% CI 2.01–22.75).Conclusions: Early coitarche has a potential effect on cervical cancer.